The change in growth, osmolyte production and antioxidant enzymes activity explains the cadmium tolerance in four tree species at the saplings stage - Zafar, Zikria; Rasheed, Fahad; Khan, Waseem Razzaq; Mohsin, Muhammad; Rashid, Muhammad Zahid; Magiman, Mohamad Maulana; Raza, Zohaib; Rosli, Zamri; Afzal, Shazia; Abu Bakar, Fauziah (Multidisciplinary Digital Publishing Institute, 2022)
Phytoremediation is a green technology; however, very few species of arid environments have been identified as hyperaccumulators and fast growers. Therefore, a greenhouse experiment was performed to evidence the phytoaccumulation potential of Conocarpus erectus, Syzygium cumini, Populus deltoides and Morus alba at the sapling stage. Six-month-old plant saplings were subjected to control (CK; 0 µM) and cadmium treatments (Cd; CdCl2; 200 µM). The results depicted that plant growth, dry biomass production (leaf and stem) and chl a, b and carotenoid contents decreased significantly in all four species under Cd treatment; however, the lowest decrease was evidenced in Conocarpus erectus. The concentration of hydrogen peroxide and superoxide radical increased significantly in all four species, with the highest increase observed in Morus alba. Osmolytes production, antioxidant enzymes activity (superoxide dismutase, peroxidase, catalase and ascorbate peroxidase) and Cd accumulation in the leaves, stem and root increased significantly in all four species under Cd treatment, with the highest increase observed in Conocarpus erectus. The translocation factor was >1 in Conocarpus erectus, Syzyngoim cumini and Populus deltoides and was <1 in Morus alba. The study revealed a better Cd tolerance in Conocarpus erectus, which was driven by the effective osmolyte balance and antioxidant enzymes mechanism.